GDNDC: An integrated system to model water-nitrogen-crop processes for agricultural management at regional scales. (December 2020) - Huang, Xiao; Ni, Shaoqiang; Wu, Chao; Zorn, Conrad; Zhang, Wenyuan; Yu, Chaoqing
Abstract: Agroecosystem modelling has increasingly focused on the integration of soil biogeochemical processes and crop growth. However, few models are available that offer high computing efficiencies for region-scale simulations, integrated decision support tools, and a structure that allows for easy extension. This paper introduces a new modelling tool to fill this gap: the GDNDC (Gridded DNDC) system for gridded agro-biogeochemical simulations. Based on the established DeNitrification and DeComposition (DNDC) model version-95, its main advancements include (i) implementation of parallel computation to significantly reduce computation time across multiple scales; (ii) a built-in parameter optimization algorithm to improve the predictive accuracy, and (iii) several decision support tools. We demonstrate each of these for county-level maize growth simulations in Liaoning Province (China) and reveal the potential of this new modelling tool to guide both long-term policy decisions regarding optimal fertilizer application and near-term crop yield forecasting for reactive decisions required in times of drought. Highlights: Parallel computing mode realized in GDNDC to improve the computing efficiency for regional-scale simulation. Multiple modules are coupled into GDNDC to enable complete end-to-end simulation for decision support. Coupler is developed in GDNDC to integrate different modules by coordinating the information exchange. GDNDC presents a new structure of agricultural modelling system for easy maintenance and extension.